Etika Keguruan dan Peranannya dalam Membangun Kepercayaan Siswa - Hadi Gunawan; Perdina Rantika (Universitas Maritim AMNI Semarang, 2025)
Teacher ethics serves as a crucial moral foundation for educators in establishing a conducive educational environment. It encompasses relationships between teachers and students, colleagues, parents, and the broader community. This article aims to examine the role of teacher ethics in building student trust, which is an essential aspect of successful teaching and learning processes. Employing a qualitative approach through literature studies, this research identifies key dimensions of teacher ethics, including justice, honesty, responsibility, and empathy, which underpin the development of student trust. The findings reveal that consistent application of teacher ethics can enhance students’ respect for their teachers, encourage active student engagement in the learning process, and foster a positive learning atmosphere. Furthermore, the trust developed strengthens the emotional connection between teachers and students, ultimately improving student learning outcomes. This study recommends the importance of teacher ethics training for educators to ensure integrity and professionalism in every educational interaction.